Measuring sexual satisfaction: An application of the latent state-trait theory - Buško, Vesna (Array, 2009)
The paper presents the development and a part of validation procedures pertaining to a new measure of sexual satisfaction. The instrument is an operationalization of a model that views sexual satisfaction as a five-dimensional concept, including the aspects of sexual activities, sexual exchange, sexual sensations, sexual presence/focusing, and emotional closeness. The scale is designed to measure sexual satisfaction rather than absence of sexual health difficulties, and intended to be equally useful in assessing sexual satisfaction of individuals in committed relationships and of those who are not in a relationship, regardless of their gender and/or sexual orientation. Scale construction and initial evaluation procedures were performed on data from several independent students’ and community samples, with repeated measurements obtained for one of the study samples. Principal component and confirmatory factor analyses performed on all sample data pointed to two interrelated underlying dimensions of sexual satisfaction interpreted as self-centred factor and partner & sexual activity centred factor. Internal consistency and reliability analyses of the two subscales and the full scale (k=20) were performed within the context of classical test theory and the latent state-trait theory (Steyer et al., 1992). Measurement invariance of the scale as a function of sex and age of subjects was tested via multi-sample confirmatory factor procedures.